2013
DOI: 10.5194/tc-7-699-2013
|View full text |Cite
|
Sign up to set email alerts
|

New estimates of Arctic and Antarctic sea ice extent during September 1964 from recovered Nimbus I satellite imagery

Abstract: Abstract. Visible satellite imagery from the 1964 Nimbus I satellite has been recovered, digitized, and processed to estimate Arctic and Antarctic sea ice extent for September 1964. September is the month when the Arctic sea ice reaches its minimum annual extent and the Antarctic sea ice reaches its maximum. Images from a three-week period were manually analyzed to estimate the location of the ice edge and then composited to obtain a hemispheric estimate. Uncertainties were based on limitations in the image an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…The polar regions have undergone major transformations over the last three decades, with satellite and in situ observations revealing a dramatic decline of Arctic summer sea ice extent and volume [Meier et al, 2013;Kwok and Rothrock, 2009], and a modest increase in winter Antarctic sea ice extent with significant spatial variability [Simpkins et al, 2013]. The magnitude and trends of such changes can only be partially captured by contemporary climate models [Stroeve et al, 2007;Jeffries et al, 2013;Tietsche et al, 2014], suggesting that important physical processes are being neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The polar regions have undergone major transformations over the last three decades, with satellite and in situ observations revealing a dramatic decline of Arctic summer sea ice extent and volume [Meier et al, 2013;Kwok and Rothrock, 2009], and a modest increase in winter Antarctic sea ice extent with significant spatial variability [Simpkins et al, 2013]. The magnitude and trends of such changes can only be partially captured by contemporary climate models [Stroeve et al, 2007;Jeffries et al, 2013;Tietsche et al, 2014], suggesting that important physical processes are being neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The 34 year record documents the seasonal and interannual evolution in the Arctic sea ice cover. Sea ice extent has decreased for all seasons, with the strongest average decline in September (84 100 km 2 per year), and a moderate average decline during May of 33 100 km 2 per year (Meier et al, 2013). After 1999After (1999After -2010, the negative decadal trend of summer sea ice extent intensified to 154 000 km 2 per year and this period stands out as one of persistent decline, with record low September minima during 2002,2005,2007, and the latest record extent of 4.41×10 6 km 2 in September 2012.…”
Section: Sea Ice Extentmentioning
confidence: 99%
“…Reconstructions based on a limited number of local observations have been carried out, resulting for example in the HadISST2 data set (Rayner et al, 2006). Inconsistencies in the transition between traditional observations and the satellite record led to a recent correction of the sea ice extent time series before 1979 (Meier et al, 2012(Meier et al, , 2013, which brought to light a large interannual variability superimposed on a rather stable summer sea ice extent from the 1950s through to the 1970s. The overall summer sea ice extent trend for the period is estimated at −6.8 % per decade.…”
Section: Introductionmentioning
confidence: 99%
“…(Sea ice area is nominally different from SIE in that it includes regions of 0-15% sea ice concentration, but tests comparing the SIE and sea ice area data reveal no noticeable difference for the season of interest.) Additionally, point estimates of SIE from the Nimbus 1, 2, and 3 satellite missions [Meier et al, 2013a;Gallaher et al, 2014] were used. The Nimbus 1 mission covered a 3 week period in September 1964, Nimbus 2 was operational from May to August 1966, and Nimbus 3 data are available for the entire May 1969 to January 1970.…”
Section: Sie Datamentioning
confidence: 99%
“…Studies have suggested that multidecadal variability may explain some of the observed trends [Fan et al, 2014], with a particular role for atmospheric teleconnections to the tropical Pacific [Ding et al, 2011], but this is hard to test in the satellite record, and useful insight may be gained from extending the sea ice record further back than 1979. Estimates of sea ice areal cover from the early NIMBUS satellite missions now provide Southern Ocean SIE as far back as 1964 [Meier et al, 2013a;Gallaher et al, 2014]. Gagne et al [2015] compared the NIMBUS 1 estimate of September 1964 Southern Ocean SIE with both models and passive microwave data and found that although there has been a slight decrease over the 50 year period, the change was not significant in the context of simulated internal variability.…”
Section: Introductionmentioning
confidence: 99%